2022
DOI: 10.1101/2022.03.14.484246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Claudin5 protects the peripheral endothelial barrier in an organ and vessel type-specific manner

Abstract: The pathogenesis of numerous diseases is characterised by disruption of the junctions that form the endothelial cell (EC) barrier, the composition of which may differ greatly between organs. However, the expression level variability and precise contribution of different junctional proteins is poorly understood. Here, we focus on organs with continuous endothelium to identify structural and functional in vivo characteristics of the EC barrier. Assembly of multiple single-cell RNAseq datasets into a single integ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Selective barrier control can be achieved through exclusive expression of junction-controlling molecules in different EC types (Hilfenhaus et al, 2018, Richards et al, 2022). However, other molecules, such as VE-cadherin (Frye et al, 2015, Hägerling et al, 2018) and EphB4 (Frye et al, 2020, Luxán et al, 2019), have been shown to have multifaceted roles in junctional regulation, despite similar expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Selective barrier control can be achieved through exclusive expression of junction-controlling molecules in different EC types (Hilfenhaus et al, 2018, Richards et al, 2022). However, other molecules, such as VE-cadherin (Frye et al, 2015, Hägerling et al, 2018) and EphB4 (Frye et al, 2020, Luxán et al, 2019), have been shown to have multifaceted roles in junctional regulation, despite similar expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…5 Charité -Universitätsmedizin Berlin, Berlin, Germany. 6 Institute for Molecular Bioscience, Division of Cell and Developmental Biology, The University of Queensland, Brisbane, Queensland, Australia. 7 Instituto de Medicina Molecular -João lobo Antunes, Faculdade de Medicina, Universidade de Lisboa, Lisboa, Portugal.…”
Section: Articlementioning
confidence: 99%
“…The maintenance of junctions and barrier function relies on junctional complexes consisting of cell-adhesion molecules formed between adjacent ECs. Tight junctions limit vascular leakage preferentially in the central nervous system (CNS) and in arteries and post-arterial capillaries in peripheral tissues [4][5][6] . Adherens junctions, formed by VE-cadherin and associated catenins, are crucial for regulating venous and capillary vascular permeability, leukocyte extravasation and collective cell migration [7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%